Estrategia de comunicación. la promoción y difusión de la oferta de maestría de la Universidad Técnica de Babahoyo - Bajaña Valencia, Luiyi Xavier (2022)
This case study exposes the communication strategies for the promotion and dissemination of the offer of master's degrees from the Technical University of Babahoyo, the master's degrees are those curricular academic programs of specialized training, which allows a professional to deepen in some area of his career, the target audience to which it is directed is mainly students who graduated in social communication in the year 2021. In addition, it is stated that strategies are those actions that are developed in the long term within an organization, which are designed to generate a different experience in the client and at the same time to be able to achieve the goals that have been set, whose sole purpose is to be able to reach each of the interested parties who are interested in completing a master's degree. For the research, the qualitative-quantitative method was used, where an observation sheet was made on the dissemination of information on social networks, interviews with experts and a survey of graduates in the aforementioned period. However, the university should carry out the strategies together with all those who make it up, it should be noted that one of the tools that should never be neglected is social networks, mainly Facebook, which is one of the social networks with the most interaction worldwide.